Projecting words, writing images : intersections of the textual and the visual in American cultural practices - Leo, John R.; Paryż, Marek (Cambridge Scholars Pub., 2011)
This gathering of essays by 20 scholars trained in comparative literatures, art history, critical theory, and American cultural studies further explores and expands the spirited and energetic field of visual cultural studies and its cognate or supplemental projects of "visual practices" and "visual literacy." Their topics and perspectives engage contemporary re-theorizations of "text," of "word" and "image," while their alignments, ruptures, slippages and aporias fall across a range of media ...